Fernando Pessoa and the book of disquiet: reflective contributions to the studies of portuguese literature - Tarlau Balieiro, Luan (Seven Editora, 2023)
The Book of Disquiet expresses a narrative consumed with anguish, observation, and infinite inquiries. Based on this context, this article aims to analyze seven excerpts from the mentioned book, written by the Portuguese poet Fernando Pessoa and signed by his semi-heteronym Bernardo Soares. Based on a qualitative methodological approach, the genius of Pessoa is confirmed by providing the writing of the real feeling in the form of prose consolidated by intense subjectivities. At the heart of this observation, it is hoped that this text will constitute a reflective construct for the studies of Portuguese Literature, to encourage discussions about the sagacity of this Portuguese poet. DOI: 10.56238/pacfdnsv1-066